Strategy for The Development of Cilembu Yam in Tegal Regency - Mulyatno, Gangsar Condro (Jurnal Indonesia Sosial Sains, 2025)
Cilembu sweet potatoes, a high-value crop in Indonesia, have seen significant expansion in Tegal Regency, yet face challenges in productivity and market competitiveness. This study aims to (1) identify driving and inhibiting factors for Cilembu sweet potato development and (2) formulate a SWOT-based strategy to enhance cultivation and marketing. A mixed-methods approach was employed, combining surveys of 84 farmers and FGDs with stakeholders (farmers, traders, government) in Bojong and Bumijawa Districts. Data were analyzed using descriptive statistics and SWOT analysis. Key drivers include favorable growing conditions, low production costs, and government support, while barriers include uneven product quality and climate risks. SWOT analysis placed the crop in Quadrant I (strengths/opportunities), recommending aggressive strategies like farmer collaboration, standardized cultivation protocols, and product diversification. The study provides actionable insights for policymakers and farmers to optimize Cilembu sweet potato agribusiness, emphasizing the need for training, technology adoption, and market linkages. Future research should assess the economic feasibility of these strategies and their scalability to other regions.